The Cambridge dictionary of Christianity: volume 1: A - J - Patte, Daniel; (1939-...) (U.S.A, 2019)
The Cambridge Dictionary of Christianity is an authoritative reference guide that enables students, their teachers, Christian clergy, and general readers alike to reflect critically upon all aspects of Christianity from its origins to the present day. Written by a team of 828 scholars and practitioners from around the world, the volume reflects the plurality of Christianity throughout its history. Key features of The Cambridge Dictionary of Christianity: -Provides a survey of the history of Christianity in the world, on each continent, and in each nation -Offers a presentation of the Christian beliefs and practices of all major Christian traditions -Highlights the different understandings of Christian beliefs and practices in different historical, cultural, religious, denominational, and secular contexts -Includes entries on methodology and the plurality of approaches that are used in the study of Christianity -Respects each Christian tradition by providing self-presentations of Christianity in each country or Christian tradition -Includes clusters of entries on beliefs and practices, each examining the understanding of a given Christian belief or practice in different historical and contemporary contexts -Presents the relationship and interaction of Christianity with other religious traditions in the world
Keywords: Christianity -- Dictionaries